Associação entre práticas alimentares de lactentes e o nível de conhecimento de pais e cuidadores acerca da alimentação complementar - Pinheiro, Mariana Castelo (2023)
Breast milk is recommended until the sixth month and from there, it should be complemented with solid foods. Food introduction must respect children’s age group. However, children have been receiving inappropriate foods early with parents/caregivers being mostly responsible for the food provision. Understanding the knowledge these providers have about food is important. In view of this, our objective is to associate infants' feeding practices with the level of knowledge of parents/caregivers about complementary feeding for children aged 6 to 23 months. This is a cross-sectional study with parents/caregivers, with their respective children assisted by a reference center for early childhood care. The research methodology was based on the collection of socioeconomic and anthropometric data and two structured questionnaires: one referring to the child's food intake in the last 24 hours; and another, about the level of knowledge of parents/caregivers about complementary feeding. In total, 87 parents/caregivers participated with most caregivers being low-income (45.98%). In general, the children had a good nutritional status and were breastfed (70.11%). Few met the dietary diversity criteria (4.6%) and the consumption of iron-rich foods (4.6%). There was a predominance of consumption of ultra-processed products (58.62%). Most parents had an adequate level of nutrition knowledge (69%). A positive correlation (⍴=0,2273) was identified between food intake and level of knowledge of parents/caregivers. It is concluded that although providers have an adequate level of knowledge, some diet indicators were not met, suggesting that other factors may interfere. It is suggested that professionals continue to advise parents and government bodies to consolidate public policies for accessibility to foods with better nutritional value.